Do Belief Differences Lead to Change in Behavior? A Study of Sri Lankan Coconut Farmers - Herath, C. S. (International Coconut Community Journal, 2012)
Technology adoption by farmers is an important factor in agricultural development in both developing and developed countries that has not been achieved over the past years. The level of technology adoption is highly dependent on farmers’ beliefs and attitudes. Therefore, adoption studies are important to identify beliefs and attitudes of farmers that affect decision making. The present study tries to explain and identify the effect of motivation on farmers’ behavior to acquire knowledge and what are their beliefs and motives that underlie adoption of technology. The theory of planned behavior provides a structure to identify farmers’ behavioral intention with respect to attitudes, subjective norms and perceived behavioral control. The Self Determination Theory provides an explanatory system for the understanding of the motivation behind volitional behavior. These two theories serve as the key methodology for the study. The results revealed that, farmers’ participation in technology dissemination programmes and their willingness to gain information and skills have a significant relationship with intrinsic motivation. Further, those farmers hold positive beliefs towards new technology adoption and innovations. Therefore, two types of extension approaches are needed to enhance the technology adoption for intrinsically motivated and extrinsically motivated farmers.